Microcoordination 2.0: Social Coordination in the Age of Smartphones and Messaging Apps. (6th October 2016) - Ling, Rich; Lai, Chih‐Hui
Abstract : This paper examines how mobile messaging apps have changed the way that people microcoordinate. It is based on five focus groups of young adults in Singapore and Taiwan. Originally, microcoordination usually assumed dyadic interaction using either SMS or mobile voice calls. Increasingly, mediated communication uses mobile messaging apps that allow multisided interactions that facilitate task‐based chat groups. Groups are easily formed but can be difficult to manage. This paper advances our understanding of microcoordination via the use of messaging apps. Specifically, it provides insights into the dual roles of instrumental and expressive interaction integral to the functioning of these messaging groups, ambient‐mediated sociation in the form of readily available communication partners in groups, and the emergence of meme‐based coordination.